2012
DOI: 10.1371/journal.pone.0044576
|View full text |Cite
|
Sign up to set email alerts
|

Thiol/Disulfide System Plays a Crucial Role in Redox Protection in the Acidophilic Iron-Oxidizing Bacterium Leptospirillum ferriphilum

Abstract: Thiol/disulfide systems are involved in the maintenance of the redox status of proteins and other molecules that contain thiol/disulfide groups. Leptospirillum ferriphilum DSM14647, an acidophilic bacterium that uses Fe2+ as electron donor, and withstands very high concentrations of iron and other redox active metals, is a good model to study how acidophiles preserve the thiol/disulfide balance. We studied the composition of thiol/disulfide systems and their role in the oxidative stress response in this extrem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 62 publications
4
32
2
Order By: Relevance
“…However, it is also found that there exist intracellular antioxidant enzyme systems (Rodrigues et al, 2010) and non-enzyme antioxidant components (Xu et al, 2016) in microorganisms to maintain the balance of ROS in cells. It is reported that the thiol/disulfide system plays a crucial role in red ox protection in L. ferriphilum (Javiera et al, 2012). Previous studies have shown that the intracellular ROS content could be regulated by exogenous chemicals such as cobalamin (Chen et al, 2016;Ferrer et al, 2016).…”
Section: Intracellular Ros Content Of Amc With Coexisting LI + and Co 2+mentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is also found that there exist intracellular antioxidant enzyme systems (Rodrigues et al, 2010) and non-enzyme antioxidant components (Xu et al, 2016) in microorganisms to maintain the balance of ROS in cells. It is reported that the thiol/disulfide system plays a crucial role in red ox protection in L. ferriphilum (Javiera et al, 2012). Previous studies have shown that the intracellular ROS content could be regulated by exogenous chemicals such as cobalamin (Chen et al, 2016;Ferrer et al, 2016).…”
Section: Intracellular Ros Content Of Amc With Coexisting LI + and Co 2+mentioning
confidence: 99%
“…It is found that the increase of the intracellular ROS content resulted from Cu 2+ accumulation can lead to the death of A. ferrooxidans (Xia et al, 2011). Fortunately, it has been proven that an intracellular ROS scavenging system exists in Leptospirillum ferrooxidans to improve the damage resistance (Javiera et al, 2012). Exogenous cobalamin has also been used to decrease the ROS content in L. ferrooxidans, and to improve cell growth and survival (Ferrer et al, 2016).…”
Section: Fe 2+mentioning
confidence: 99%
See 1 more Smart Citation
“…is an autotrophic obligate acidophilic bacterium that catalyzes dissimilatory Fe(II) oxidation. It serves as a model bacterium to elucidate the mechanisms used by acidophilic microorganisms to thrive under highly oxidative conditions [16][17][18][19]. Thirteen tfp genes (formerly trx) coding for predicted TFPs have been identified in Leptospirillum spp.…”
Section: Introductionmentioning
confidence: 99%
“…Thirteen tfp genes (formerly trx) coding for predicted TFPs have been identified in Leptospirillum spp. [18]. Exposure of Leptospirillum ferriphilum to ROS-generating compounds resulted in a concomitant increase in thioredoxin activity.…”
Section: Introductionmentioning
confidence: 99%